Pengembangan Aplikasi Katalog dan Manajemen Dokumen bertipe PDF untuk Ebook berbasis Website - Ridwan Subula; Ahmad Rio Adriansyah (LPPM STT Terpadu Nurul Fikri, 2021)
This research focuses on developing a pdf ebook digital file catalog provided by online ebook providers to store, document, and disseminate electronic books to the public. This study aims to build a good, orderly, and neat digital file catalog with a modern appearance. This development research adapts the Action Research method with planning, acting, observing, and reflecting procedures. The method used for data collection uses observation, questioner, classification, and documentation. The results of this study conclude that ebooks or electronic books and digital files are essential in today's modern era, with the development of website-based digital catalog applications, so that ebooks and digital files that have documents can fine on a one platform website-based without the need to go through a search complicated and avoid out-of-date file provider websites. So that users will get a new experience in accessing nor studying the available digital files.